A Case Study of Panthi Dairy Pvt. Ltd. Industrial District, Pokhara - Pokharel, Dhruba Raj (Saptagandaki Journal, 2017)
A case study of Panthi Dairy Pvt. Ltd. was conducted to bring out the live situations and experiences of an entrepreneur developing the dairy sector. The issues raised in this case are heart breaking as well as heartwarming. The present case study of Panthi Dairy Pvt. Ltd. may contribute to the students and faculties of management in undergraduate and graduate level studying at different universities in Nepal. The experiences shared with the Chair of Panthi Dairy Pvt. Ltd. teach us that every failure is the basement for success. Despite of all other factors, self-study, regulation and control are the major ingredients that contribute to entrepreneurial success. The Saptagandaki Journal Vol.8 2017: 42-46